Student Learning Outcomes on Ecology and Biodiversity with the Construcvism Approach Learning Discovery Models - Avif Intan Linawati; Dyah Rini Indriyanti; Saiful Ridlo (Journal of Innovative Science Education, 2023)
The research aims to analyze student learning outcomes, analyze student activities, analyze student responses and analyze teacher responses with a constructivist approach to discovery learning models. The form of research is pre experimental design, pre test-post test control group design. The population in this study were all junior high students of class VII even semester of SMP N 1 Brangsong, while the research sample was class VIIA and VIIB. Learning outcomes were analyzed using the t-test, while student activities, student responses and teacher responses were analyzed descriptively. The results showed that the gainscore of the experimental class was 31.54 while that of the control class was 25.92, while the significant value of the T-test was 0.000, the activity of the experimental class students was 93.6%, the student response was 89.69% positive while 10.31% was negative and the teacher's response was 85. 7% strongly agree. The conclusion of this study is that the results of student learning on ecology and biodiversity with a constructivist approach to the discovery learning model are better than the control class, the material for ecology and biodiversity with a constructivism approach, the discovery learning model makes students more active, students' responses Ecology and biodiversity material using a constructivist approach to the discovery learning model is positive and the teacher's response to the material on ecology and biodiversity using a constructivist approach to discovery learning model is positive, so it is very agreeable to be applied.